2015
DOI: 10.3390/jmse3010100
|View full text |Cite
|
Sign up to set email alerts
|

Impulse Wave Generation: Comparison of Free Granular with Mesh-Packed Slides

Abstract: Slides generating impulse waves are currently generated using either block models or free granular material impacting a water body. These procedures were mainly developed to study plane impulse waves, i.e., wave generation in a rectangular channel. The current VAW, ETH Zurich, research is directed to the spatial impulse wave features, i.e., waves propagating in a wave basin. The two wave generation mechanisms mentioned above complicate this process for various reasons, including experimental handling, collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Mesh-packed slides were applied, allowing for a simplified handling similar to rigid slides while maintaining a granular matrix and deformability. Evers and Hager (2015a) showed that the impulse wave characteristics generated by this type of slide are predictable with empirical equations derived from experiments with free granular slides within a similar scatter range, e.g. ±30% for the wave height, provided that the slide centroid velocity is the reference velocity in both cases.…”
Section: Methodsmentioning
confidence: 72%
“…Mesh-packed slides were applied, allowing for a simplified handling similar to rigid slides while maintaining a granular matrix and deformability. Evers and Hager (2015a) showed that the impulse wave characteristics generated by this type of slide are predictable with empirical equations derived from experiments with free granular slides within a similar scatter range, e.g. ±30% for the wave height, provided that the slide centroid velocity is the reference velocity in both cases.…”
Section: Methodsmentioning
confidence: 72%
“…Empirical equations for the maximum wave amplitude generated by a landslide have been developed for a variety of experimental conditions. Methods of simulating the landslide have included solid blocks [ Kamphuis and Bowering , ; Panizzo et al ., ; Sælevik et al ., ; Heller and Spinneken , ] or bagged (or mesh‐packed) granular materials [ Slingerland and Voight , ; Evers and Hager , ] released on a low friction surface under gravitational acceleration. Loose granular materials have also been used in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical equations for the maximum wave amplitude generated by a landslide have been developed for a variety of experimental conditions. Methods of simulating the landslide have included solid blocks [Kamphuis and Bowering, 1970;Panizzo et al, 2005b;Saelevik et al, 2009;Heller and Spinneken, 2013] or bagged (or mesh-packed) granular Key Points: A physical model is used to investigate waves from long and thin landslides generated using a large granular mass that is released down slope In long and thin granular landslides, only a fraction of the landslide volume contributes to the generation of the first and highest wave Wave shapes, maximum amplitudes, and runup elevations are quantified relative to landslide parameters materials [Slingerland and Voight, 1982;Evers and Hager, 2015] released on a low friction surface under gravitational acceleration. Loose granular materials have also been used in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…For the wave generation, mesh-packed granular material was used as an alternative to free granular material slides mainly in view of experimental effort and handling. Evers and Hager (2015) showed that waves generated by mesh-packed slides are physically similar to these generated with free granular material. Two different granules were loosely filled into bags of sifting medium, each.…”
Section: Methodsmentioning
confidence: 95%